2009
DOI: 10.1038/aps.2009.177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of betulinic acid on the regulation of Hiwi and cyclin B1 in human gastric adenocarcinoma AGS cells

Abstract: Aim:To investigate the effect of betulinic acid (BA) on the proliferation, apoptosis and cell cycle of gastric adenocarcinoma cell AGS in vitro and elucidate the underlying mechanisms. Methods: The effect of BA on the proliferation of AGS cells was measured by using 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium (MTT) assay. Apoptosis was analyzed by using Annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI) double-labeled flow cytometry (FCM) and Hoechst 33258 staining. The influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…It also decreased GLI1, GLI2, PTCH1, and IGF2 expression as well as hedgehog-response in vitro. It also caused retarded the growth of RMS-13 xenografts by causing apoptosis and down-regulating GLI1 expression without affecting the microvascular density, cell proliferation, and myogenic differentiation unaffected [143]; 4) Induces apoptosis through the mitochondrial pathway and inducing cytochrome c…”
Section: Sr Nomentioning
confidence: 99%
“…It also decreased GLI1, GLI2, PTCH1, and IGF2 expression as well as hedgehog-response in vitro. It also caused retarded the growth of RMS-13 xenografts by causing apoptosis and down-regulating GLI1 expression without affecting the microvascular density, cell proliferation, and myogenic differentiation unaffected [143]; 4) Induces apoptosis through the mitochondrial pathway and inducing cytochrome c…”
Section: Sr Nomentioning
confidence: 99%
“…Multiple mechanisms have been reported for the potent anticancer activity of BA [21] . In a previous study, we demonstrated that BA induced cell cycle arrest and apoptosis in human gastric adenocarcinoma AGS cells through the downregulation of Hiwi and Cyclin B1 [17] . In the present study, BA inhibited cell proliferation in multiple myeloma KM3 cells and induced apoptosis in a dose-dependent manner.…”
Section: Wwwchinapharcom Yang L J Et Almentioning
confidence: 99%
“…Various mechanisms have been reported for the extensive anticancer activity of BA, including directly triggering mitochondrial membrane permeabilization [20] , regulating Bcl-2 family proteins [21] , downregulating Hiwi expression [17] and suppressing the activation of the STAT3 pathway through the induction of the protein tyrosine phosphatase SHP-1 [19] . However, there are no reports as to whether BA has any effects on cancer cell autophagy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA content of cells was analyzed using PI staining, followed by flow cytometry analysis (FACS Calibur, BD Biosciences, San Diego, CA, USA), as previously described (Yang et al, 2010).…”
Section: Cell Cycle Analysismentioning
confidence: 99%